(untitled) (Palíndromo, 2020)
The text investigates the trousseau of mariage (trousseau de mariage) as a legitimizing device of norms related to female sexual education. Two vectors are questioned, scientia sexualis and embroidery.The embroidery tékhne (τέχνη) allows to discuss the constitution of female subjectivities and naturalized by historically determined normative standards.